Management of Assets and Follow-Up the Findings of the Audit Board to Increase Financial Performance of Local Governments - Ridha Yamin; Masdar Mas'ud; Sylvia Sjarlis (International Ecsis Association, 2022)
The dependence of most local governments on the central government in funding regional spending is still a problem in Indonesia. Although the regional autonomy system has been implemented, including in terms of regional financial management, local governments still have difficulty in implementing efficient regional spending. This effort is done so that the financial management of local governments can be implemented efficiently. This research aims to find out the impact of the size of local governments, audit findings and follow-up of the recommendations of The Audit Board of the Republic of Indonesia on the financial performance of local governments This study uses a quantitative approach by testing hypotheses using multiple regression analysis methods in cross sectional data. The study used data from local government performance reports in 2019. The study analyses 406 district/city governments report in Indonesia. The results showed that: 1) There is a positive and significant influence on the size of local governments on the financial performance of local governments in Indonesia; 2) There are negative and significant influences on the findings of examination of the financial performance of local governments in Indonesia; 3) There is a positive and significant influence on follow-up recommendations of examination results on the financial performance of local governments in Indonesia. The results implication is that efficiency of local government asset and follow-up of audit findings of the Audit Board Republic of Indonesia can improve the financial performance of local governments.